A Lower-Back Exoskeleton With a Four-Bar Linkage Structure for Providing Extensor Moment and Lumbar Traction Force - Chaerim Moon; Jangho Bae; Jaewon Kwak; Daehie Hong (IEEE, 2022)
Lower back pain and related injuries are prevalent and serious problems in various industries, and high compression force to the lumbosacral (L5/S1) region has been known as one of the key factors. Previous research on passive lower back exoskeletons focused on reducing lumbar muscle activation by providing an extensor moment. Additionally, lumbar traction forces can reduce the compression force, and is a common treatment method for lower back pain in clinics. In this paper, we propose a novel passive lower back exoskeleton that provides both extensor moment and lumbar traction force. The working principle of the exoskeleton, extending the coil springs during lumbar flexion, and its design criteria regarding the amount of each force element were provided. The kinematic model explained its operation, and the dynamic simulation estimated its performance and validated its satisfaction with the design criteria. The biomechanical model provided a brief insight into the expected exoskeleton’s effect on the reduced lower back compression force. Ten subjects performed static holding and dynamic lifting tasks, and the generated force elements in two directions, parallel and perpendicular to the trunk, were evaluated using a force sensor and electromyography sensors, respectively. The experiment demonstrated a pulling force opposite to the direction of intradiscal pressure and reduced erector spinae activation. This implies the effect of wearing the exoskeleton to decrease the intervertebral pressure during static back bending or heavy lifting tasks.